2021
DOI: 10.3389/fimmu.2021.705436
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role for Atg5 in Microbiota-Dependent Foxp3+ RORγt+ Treg Cell Preservation to Maintain Intestinal Immune Homeostasis

Abstract: Autophagy is an evolutionary conserved catabolic pathway that ensures the degradation of intracellular components. The autophagic pathway is regulated by autophagy-related (Atg) proteins that govern formation of double-membraned vesicles called autophagosomes. Autophagy deficiency in regulatory T (Treg) cells leads to increased apoptosis of these cells and to the development of autoimmune disorders, predominantly characterized by intestinal inflammation. Recently, RORγt-expressing Treg cells have been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Kabat et al reported that Atg16l1-deficient CD4 + T cells show a reduced population of Treg cells ( Kabat et al, 2016 ). Aged Atg16l1 f/f CD4-Cre mice and aged Atg5 f/f Foxp3-Cre mice showed increased inflammation in the colon and greater weight loss compared with normal control mice ( Kabat et al, 2016 ; Plaza-Sirvent et al, 2021 ).…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 91%
“…Kabat et al reported that Atg16l1-deficient CD4 + T cells show a reduced population of Treg cells ( Kabat et al, 2016 ). Aged Atg16l1 f/f CD4-Cre mice and aged Atg5 f/f Foxp3-Cre mice showed increased inflammation in the colon and greater weight loss compared with normal control mice ( Kabat et al, 2016 ; Plaza-Sirvent et al, 2021 ).…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 91%
“…The transplantation of healthy human feces can ameliorate DSS-induced UC in GF mice and increase the number of IL-17-producing Tregs, illustrating that gut probiotics can enhance UC by promoting IL-17-producing Treg differentiation [136]. Moreover, mice lacking Arkadia or Atg5-mediated differentiation of IL-17-producing Tregs display intestinal inflammation [13,61]. It has also been reported that in the context of inflammatory bowel disease, ILC3s can alleviate intestinal inflammation by promoting IL-17-producing Treg differentiation [168].…”
Section: The Amelioration Of Ibd By Promoting Il-17-producing Treg Di...mentioning
confidence: 99%
“…IL-17-producing Tregs have been identified not only in peripheral blood and lymphoid tissue but also in various organs, including the intestine [ 13 ], spleen [ 14 ], lymph nodes [ 14 ], lung [ 15 ], liver [ 15 ], kidney [ 16 ], and other tissues. In contrast to conventional Tregs, IL-17-producing Tregs exhibit distinct phenotypic characteristics, characterized by high levels of RORγT, inducible co-stimulator (ICOS), cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), and CD103 expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, RORγt + Tregs may be important factors in limiting microbial dysbiosis and intestinal inflammation [75], and the production of RORγt + Tregs depends on the presence of gut microbes, including Clostridium, and other members of Firmicutes, Bacteroidetes, and Proteobacteria support their differentiation [53,58].…”
Section: Scfas Enhanced the Expression Of Rorγt + Treg Cellsmentioning
confidence: 99%